What do Cochrane systematic reviews say about the clinical effectiveness of screening and diagnostic tests for cancer? - Bueno, André Tito Pereira; Capelasso, Vladimir Lisboa; Pacheco, Rafael Leite; Latorraca, Carolina de Oliveira Cruz; Castria, Tiago Biachi de; Pachito, Daniela Vianna; Riera, Rachel (São Paulo Medical Journal, 2017)
CONTEXT AND OBJECTIVE: The purpose of screening tests for cancer is to detect it at an early stage in order to increase the chances of treatment. However, their unrestrained use may lead to unnecessary examinations, overdiagnosis and higher costs. It is thus necessary to evaluate their clinical effects in terms of benefits and harm. DESIGN AND SETTING: Review of Cochrane systematic reviews, carried out in the Discipline of Evidence‑Based Medicine, Escola Paulista de Medicina, Universidade Federal de São Paulo. METHODS: Cochrane reviews on the clinical effectiveness of cancer screening procedures were included. Study titles and abstracts were independently assessed by two authors. Conflicts were resolved by another two authors. Findings were summarized and discussed. RESULTS: Seventeen reviews were selected: fifteen on screening for specific cancers (bladder, breast, colorectal, hepatic, lung, nasopharyngeal, esophageal, oral, prostate, testicular and uterine) and two others on cancer in general. The quality of evidence of the findings varied among the reviews. Only two reviews resulted in high-quality evidence: screening using low-dose computed tomography scans for high-risk individuals seems to reduce lung cancer mortality; and screening using flexible sigmoidoscopy and fecal occult blood tests seems to reduce colorectal cancer mortality. CONCLUSION: The evidence found through Cochrane reviews did not support most of the commonly used screening tests for cancer. It is recommended that patients should be informed of the possibilities of false positives and false negatives before they undergo the tests. Further studies to fully assess the effectiveness of cancer screening tests and adverse outcomes are required.